2009
DOI: 10.1002/ptr.2680
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Citrus paradisi extract and juice on arterial pressure both in vitro and in vivo

Abstract: Citrus paradisi (grapefruit) consumption is considered as beneficial and it is popularly used for the treatment of a vast array of diseases, including hypertension. In the present study, the coronary vasodilator and hypotensive effects of Citrus paradisi peel extract were assessed in the Langendorff isolated and perfused heart model and in the heart and lung dog preparation. In both models, Citrus paradisi peel extract decreased coronary vascular resistance and mean arterial pressure when compared with control… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(19 citation statements)
references
References 29 publications
0
18
1
Order By: Relevance
“…In recent years, the phenolic compounds present in grapefruit have been investigated, and some publications have suggested that they could play an important role in the antioxidant capacity of grapefruit juice (Gorinstein et al, 2005;Xu et al, 2008), which has been related with the prevention of different chronic diseases including heart disease, obesity, diabetes, cardiovascular diseases and cancer (Mertens-Talcott, Zadezensky, De Castro, Derendorf & Butterweck, 2006;Vanamala, Reddivari, Yoo, Pike, & Patil, 2006;Díaz-Ju arez et al, 2009). Some epidemiological studies also pointed to the consumption of grapefruit brings benefits in weight loss and improve lipid metabolism (Dow, Going, Chow, Patil, & Thomson, 2012;Gorinstein et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, the phenolic compounds present in grapefruit have been investigated, and some publications have suggested that they could play an important role in the antioxidant capacity of grapefruit juice (Gorinstein et al, 2005;Xu et al, 2008), which has been related with the prevention of different chronic diseases including heart disease, obesity, diabetes, cardiovascular diseases and cancer (Mertens-Talcott, Zadezensky, De Castro, Derendorf & Butterweck, 2006;Vanamala, Reddivari, Yoo, Pike, & Patil, 2006;Díaz-Ju arez et al, 2009). Some epidemiological studies also pointed to the consumption of grapefruit brings benefits in weight loss and improve lipid metabolism (Dow, Going, Chow, Patil, & Thomson, 2012;Gorinstein et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…GJ has been reported to decrease diastolic and systolic arterial pressure in normotensive and hypertensive subjects, suggesting a potential effect for the treatment of hypertension [5]. Rats given grapefruit increased their antioxidant status as well as their bone density due to bone mineral deposition and slowed-down bone turnover, suggesting then a beneficial role of this fruit in osteoporosis [6]; also, extracts from its seeds tested in diabetic rats lowered the content of glucose, triglycerides, cholesterol and low density lipoprotein-cholesterol to a level similar to that obtained with the drug, metformin, an action which suggests a useful effect of grapefruit in the management of diabetic patients [4].…”
Section: Discussionmentioning
confidence: 99%
“…The plant possesses carbohydrates, lipids, proteins, vitamins, minerals and other compounds such as flavonoids, coumarins and hydroxicynamic acids. The consumption of grapefruit has been suggested to give rise to beneficial activities regarding cardiac diseases, diabetes, bone quality and urinary tract infections [4][5][6][7].…”
Section: Introductionmentioning
confidence: 99%
“…The phenolic extract from grapefruit peels was shown to inhibit α-amylase-, α-glucosidase-and angiotensin-I-converting enzymes in a dose-dependent manner [44]. In another study, a grapefruit peel extract was able to decrease coronary vascular resistance and the mean arterial pressure in a Langendorff isolated and perfused heart model [45]. Nevertheless, most of these studies used raw extract of citrus peel.…”
Section: Discussionmentioning
confidence: 99%